Microbes Associated with Freshly Prepared Juices of Citrus and Carrots - Kamal Rai Aneja; Romika Dhiman; Neeraj Kumar Aggarwal; Vikas Kumar; Manpreeet Kaur (International Journal of Food Science)
Fruit juices are popular drinks as they contain antioxidants, vitamins, and minerals that are essential for human being and play important role in the prevention of heart diseases, cancer, and diabetes. They contain essential nutrients which support the growth of acid tolerant bacteria, yeasts, and moulds. In the present study, we have conducted a microbiological examination of freshly prepared juices (sweet lime, orange, and carrot) by serial dilution agar plate technique. A total of 30 juice samples were examined for their microbiological quality. Twenty-five microbial species including 9 bacterial isolates, 5 yeast isolates, and 11 mould isolates were isolated from juices. Yeasts and moulds were the main cause of spoilage of juices. Aspergillus flavus and Rhodotorula mucilaginosa were observed in the maximum number of juice samples. Among bacteria Bacillus cereus and Serratia were dominant. Escherichia coli and Staphylococcus aureus were detected in few samples. Candida sp., Curvularia, Colletotrichum, and Acetobacter were observed only in citrus juice samples. Alternaria, Aspergillus terreus, A. niger, Cladosporium, and Fusarium were also observed in tested juice samples. Some of the microorganisms detected in these juice samples can cause disease in human beings, so there is need for some guidelines that can improve the quality of fruit juices.